Immediate and residual effect of tobacco powder compost and of NPK on N2O emissions and on N use in a wheat/corn crop succession - Pâmela Oruoski; Celso Aita; Stefen Barbosa Pujol; Heitor Luís Santin Bazzo (Revista Brasileira de Ciência do Solo)
ABSTRACT Organic fertilization with tobacco powder compost produced via solid-state fermentation (SSF) is a recent practice that needs to be evaluated through research. This study aimed to evaluate the effect of two nitrogen sources – tobacco powder compost or mineral fertilizer (NPK) – and of compost doses on N use and loss in an immediate and residual way in a wheat/corn crop succession in a subtropical Argissolo. The wheat/corn crop succession was established after three successive fertilizer applications with different doses of the compost and of NPK. The following treatments were evaluated: control without application of the compost or mineral fertilizer (C0); mineral fertilization (NPK); and three doses of tobacco powder compost calculated to supply half (C50), the same amount (C100), and double (C200) the N applied via mineral NPK fertilization. To evaluate the residual effect of the fertilizer applications, the C50, C100, C200, and NPK treatments gave rise to additional treatments that did not receive more fertilization: rC50, rC100, rC200, and rNPK, respectively. The C0 generated an additional treatment that came to receive compost, identified as C0-C100. Yield and N accumulation in the aerial part of wheat and corn and N2O emission were evaluated throughout the two crop periods. Compost, in comparison to NPK, maintained the grain yield of wheat (3.0 vs2.5 Mg ha-1) and of corn (10.2 vs 9.5 Mg ha-1) and increased N accumulation in the wheat plants (96 vs 68 kg ha-1) and corn plants (191 vs 164 kg ha-1). Compost increased cumulative N2O emissions by up to three times compared to NPK (6.84 vs 1.93 kg N-N2O ha1 yr1). Increasing the compost dose increased cumulative N2O emissions by 52 % (9.36 vs 6.16 ha-1 yr-1); however, it did not change the emission factor (EF) of N2O, the yield-scaled emission, or N use efficiency. The compost residual effect increased wheat yield up to 93 % and corn yield up to 102 %, whereas no residual effect was observed from NPK. Compost applied on the previous crops did not affect N2O emissions in wheat or in corn; consequently, a residual effect did not impact the EF of N2O. Therefore, tobacco powder compost has the potential to replace mineral fertilization in wheat and in corn. Considering its residual effect is an important strategy to optimize its use and mitigate N2O emissions to the atmosphere.